Melanggar Makna Prinsip Kooperatif Grice Dalam Wawancara Eksklusif Dengan Chris Martin Dari Coldplay Di Acara Talkshow Mata Najwa - Sari, Ririn Novita; Rullyanti, Merry; Pradana, Ami (UNIVED Press, Universitas Dehasen Bengkulu, 2024)
The focus of this research was to analyse the extent of flouting maxim of Grice’s Cooperative principle done by Chris Martin, vocalist of the band Coldplay and analyse the types of flouting Grice’s Cooperative principle used by guests and their reasons, this interview hosted by NajwaShihab in the Mata Najwa program which is a highly interactive talk show entitled